Dendritic Cells Transfected with MHC Antigenic Determinants of CBA Mice Induce Antigen-Specific Tolerance in C57Bl/6 Mice - Sergey V. Sennikov; Valeriy P. Tereshchenko; Vasiliy V. Kurilin; Julia A. Shevchenko; Julia A. Lopatnikova; Alexander N. Silkov; Amir Z. Maksyutov; Maria S. Kuznetsova; Nadezda Y. Knauer; Aleksey S. Bulygin; Julia N. Khantakova (Journal of Immunology Research)
Background. Nonspecific immunosuppressive therapy for graft rejection and graft-versus-host disease (GVHD) is often accompanied by severe side effects such as opportunistic infections and cancers. Several approaches have been developed to suppress transplantation reactions using tolerogenic cells, including induction of FoxP3+ Tregs with antigen-loaded dendritic cells (DCs) and induction of CD4+IL-10+ cells with interleukin IL-10-producing DCs. Here, we assessed the effectiveness of both approaches in the suppression of graft rejection and GVHD. Methods. IL-10-producing DCs were generated by the transfection of DCs with DNA constructs encoding mouse IL-10. Antigen-loaded DCs from C57BL/6 mice were generated by transfection with DNA constructs encoding antigenic determinants from the H2 locus of CBA mice which differ from the homologous antigenic determinants of C57BL/6 mice. Results. We found that both IL-10-producing DCs and antigen-loaded immature DCs could suppress graft rejection and GVHD but through distinct nonspecific and antigen-specific mechanisms, respectively. Discussion. We provide data that the novel approach for DCs antigen loading using DNA constructs encoding distinct homologous determinants derived from major histocompatibility complex genes is effective in antigen-specific suppression of transplantation reactions. Such an approach eliminates the necessity of donor material use and may be useful in immunosuppressive therapy side effects prevention.